2007
DOI: 10.1055/s-2007-981595
|View full text |Cite
|
Sign up to set email alerts
|

Silyamandin, a New Flavonolignan Isolated from Milk Thistle Tinctures

Abstract: Our investigations into the stability of tincture preparations of milk thistle fruit [ Silybum marianum L. Gaertn. (Asteraceae)] have led to the characterization of a new flavonolignan 4-(4-hydroxy-3-methoxyphenyl)-7-[(2 R,3 R)-3,5,7-trihydroxy-4-oxochroman-2-yl]-1-oxo-1,3,3a,4,5,7a-hexahydro-2-benzofuran-5-carboxylic acid called silyamandin (1). Incubation of the tincture at 40 degrees C for 3 months resulted in an increase in the level of this compound, as observed in the LC/DAD silymarin profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 3 publications
(4 reference statements)
1
12
0
Order By: Relevance
“…The observed characteristic J -patterns included several non-first order resonances and were fully consistent with the structure of silyamandin. While the data align well with those first reported by MacKinnon et al [16], several of the previously reported coupling values and multiplicities require revision. Table 3 provides all chemical shifts and a comprehensive J -correlation map of silyamandin is represented in the form of a Quantum Interaction and Linkage Table (QuILT) [18].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The observed characteristic J -patterns included several non-first order resonances and were fully consistent with the structure of silyamandin. While the data align well with those first reported by MacKinnon et al [16], several of the previously reported coupling values and multiplicities require revision. Table 3 provides all chemical shifts and a comprehensive J -correlation map of silyamandin is represented in the form of a Quantum Interaction and Linkage Table (QuILT) [18].…”
Section: Resultssupporting
confidence: 89%
“…This flavonolignan was recently isolated from a tincture of S. marianum that had been incubated at 40 °C for 3 months [16] and postulated to have been formed via oxidative degradation of silydianin. The broad singlet at 6.11 ppm corresponding to the H-6′ of silyamandin, well-separated from other signals in the spectra of S. marianum extracts, was used to determine the silyamandin content.…”
Section: Resultsmentioning
confidence: 99%
“…20–35%), flavonoids, and various other polyphenolic compounds in smaller amounts. The Silymarin complex includes silybin (silibinin) as major component, silychristin, isosilybin, and silydianin among the other flavonolignans, as well as the flavonoid taxifolin (Szilági et al, 1981 ; Lee and Liu, 2003 ; Kroll et al, 2007 ; MacKinnon et al, 2007 ). Silymarin has been used for more than 2000 years for the improvement of liver conditions and against hepato-toxicity in general (Post-White et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Â 150 mm; YMC, Kyoto, Japan), using 50% MeOH/H 2 O, to yield silibinin A (1, 16 mg from 240 mg of silymarin, 6.7%) 16) and silibinin B (2, 25 mg from 240 mg of silymarin, 10%), 16) and using 40% MeOH/H 2 O to yield silydianin (3, 31 mg from 370 mg of silymarin, 8.4%. 17) The second fraction was separated in a YMC-Pack ODS-AL column (20 mm i.d. Â 150 mm; YMC) using 40% MeOH/H 2 O to give (þ)-taxifolin (4, 6.7 mg from 310 mg of silymarin, 2.2%), 18) isosilychristin (5, 3.9 mg from 310 mg of silymarin, 1.3%), 19) and silychristin (6, 26 mg from 310 mg of silymarin, 8.4%) 20) (Fig.…”
mentioning
confidence: 99%
“…The structures of these compounds were confirmed by 1 H-NMR (AVANCE III 500, ref. tetramethylsilane, Bruker, Germany), [16][17][18][19][20] EI-MS (JMS-600H, 70 eV, 300 mA, JEOL, Tokyo, Japan), and specific optical rotation (P-2200, Jasco, Tokyo, Japan).…”
mentioning
confidence: 99%